CARBON ABSORPTION POTENTIAL IN MANGROVE ECOSYSTEM IN BORONGKALUKUA, MAROS REGENCY, SOUTH SULAWESI, INDONESIA - Salwa, Sausan As; Rukminasari, Nita; Alam, Jamaluddin Fitrah; Rahim, Sri Wahyuni (Universitas Medan Area, 2025)
Mangrove ecosystems are essential in mitigating climate change through Carbon storage in sediments. This study aims to analyze the bulk density values, carbon concentration, and Carbon storage and absorption in mangrove sediments in Borongkalukua, Maros Regency. Sampling was carried out at five sediment depths (0-10 cm, 10-20 cm, 20-30 cm, 30-40 cm, and 40-50 cm) using the Loss on Ignition (LOI) method and analyzed statistically using one-way and two-way ANOVA. The results showed an average bulk density value of 0.33 g/cm³, with the highest value at a depth of 30-40 cm (0.28 g/cm³). Furthermore, the average Carbon concentration was 11.37%, with the highest value at a depth of 40-50 cm (20.50%) and the lowest at 0-10 cm (1.98%), with no significant differences between depths (p-value > 0.05). Meanwhile, Carbon storage in sediment reached 2,423.77 tons/ha. Total absorption reaching 8,895.23 tons/ha. In conclusion, sediment depth affects carbon accumulation, with higher carbon content in deeper layers due to the sedimentation process and minimal decomposition. This study emphasizes the importance of mangrove conservation in supporting Carbon storage and climate change mitigation.